Pancasila in the Context of Indonesian Legal Reform: A Critical Evaluation and International Debate - Siregar, Elfrida Herawati; Utomo, Cahyo Budi; Sholeh, Muh (Journal of Law and Legal Reform, 2024)
Pancasila, as Indonesia’s foundational ideology, plays a central role in shaping the country’s legal framework. However, its application in contemporary legal reform presents significant challenges amidst evolving societal dynamics and international legal debates. This study critically evaluates the incorporation of Pancasila within Indonesia’s legal reform processes, emphasizing its relevance in addressing domestic and global tensions. The urgency of this research stems from growing critiques of Indonesia’s legal alignment with international standards while preserving its ideological roots. Concurrently, the rise of globalization and pluralism demands an adaptive yet principled approach to Pancasila’s integration into modern legal structures. This research provides a novel perspective by analyzing specific legal cases and policy reforms where Pancasila principles have been contested or reinterpreted. Through a doctrinal and socio-legal analysis, the study examines the compatibility of Pancasila with contemporary global legal norms, including human rights, environmental law, and economic governance. Furthermore, it explores Indonesia’s engagement in international debates on the role of ideology in law, offering insights into the challenges of balancing national identity with global expectations. The findings reveal that while Pancasila remains a unifying framework, its inconsistent application risks undermining its potential to guide inclusive and sustainable legal reforms. This study contributes to the broader discourse by proposing actionable recommendations for harmonizing Pancasila with international legal developments while safeguarding Indonesia’s ideological integrity. It serves as a critical resource for scholars, policymakers, and practitioners navigating the intersection of ideology, law, and globalization.